2020
DOI: 10.1128/iai.00907-19
|View full text |Cite
|
Sign up to set email alerts
|

LuxS/AI-2 Quorum Sensing System in Edwardsiella piscicida Promotes Biofilm Formation and Pathogenicity

Abstract: LuxS/AI-2 is an important quorum sensing system which affects the growth, biofilm formation, virulence, and metabolism of bacteria. LuxS is encoded by the luxS gene, but how this gene is associated with a diverse array of physiological activities in Edwardsiella piscicida (E. piscicida) is not known. Here, we constructed an luxS gene mutant strain, the △luxS strain, to identify how LuxS/AI-2 affects pathogenicity. The results showed that LuxS was not found in the luxS gene mutant strain, and this gene deletion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 49 publications
0
12
1
Order By: Relevance
“…Notably, in our study the luxS gene was detected in about 98% of the tested isolates. Using a rat model of middle ear challenge, Yadav et al (2018) demonstrated that the functional defect in LuxS, leading to the reduced colonization capability of pneumococci in vivo [29]. However, in contrast to our results, Pakhshan et al [30] concluded that the susceptible isolates to antibiotics tend to form stronger bio lms compared with the resistant strains.…”
Section: Discussioncontrasting
confidence: 89%
“…Notably, in our study the luxS gene was detected in about 98% of the tested isolates. Using a rat model of middle ear challenge, Yadav et al (2018) demonstrated that the functional defect in LuxS, leading to the reduced colonization capability of pneumococci in vivo [29]. However, in contrast to our results, Pakhshan et al [30] concluded that the susceptible isolates to antibiotics tend to form stronger bio lms compared with the resistant strains.…”
Section: Discussioncontrasting
confidence: 89%
“…Notably, in our study the luxS gene was detected in about 98 % of the tested isolates. Using a rat model of middle ear challenge, Yadav et al demonstrated that a functional defect in LuxS, leading to the reduced colonization capability of pneumococci in vivo [28]. Our results exhibited that resistance to antimicrobial agents was higher in K. pneumoniae which is biofilm producer than non-biofilm producer.…”
Section: Discussionmentioning
confidence: 48%
“…A recent paper introduced that Edwardsiella exist in aquatic environments either as individual planktonic cells or in communal biofilms [ 31 ]. However, biofilm production by Edwardsiella has been only related to its life as a pathogen for vertebrate animals [ 32 , 33 ]. Moreover, E. piscicida and E. tarda have hardly been isolated from surface water in natural environments, and work on this subject is limited.…”
Section: Discussionmentioning
confidence: 99%